The effect of the North Atlantic Subpolar Front as a boundary in pelagic biogeography decreases with increasing depth and organism size. (November 2015) - Vecchione, Michael; Falkenhaug, Tone; Sutton, Tracey; Cook, April; Gislason, Astthor; Hansen, Hege Øverbø; Heino, Mikko; Miller, Peter I.; Piatkowski, Uwe; Porteiro, Filipe; Søiland, Henrik; Bergstad, Odd Aksel
Highlights: The Subpolar Front is distinct along its northern edge but to the south it forms a more diffuse zone. North-south water-mass hydrography is strongest down to depths of 500–800 m. The frontal biogeographic signature is strong near the surface but decreases with greater depth. This strong surface feature is therefore not a good predictor of deep pelagic biogeography. Abstract: Broad-scale patterns in the distribution of deep-sea pelagic species and communities are poorly known. An important question is whether biogeographic boundaries identified from surface features are important in the deep mesopelagic and bathypelagic. We present community analyses of discrete-depth samples of mesozooplankton and micronekton to full-ocean depth collected in the area where the Mid-Atlantic Ridge is crossed by the Subpolar Front. The results show that the distributional discontinuity associated with the front, which is strong near the surface, decreases with increasing depth. Both the frontal separation near the surface and the community convergence at increasing depths were clearer for mesozooplankton than for micronekton.